Vegetative Morphology and Starch Production Among Sago Plants (Metroxylon spp.) in Kepulauan Meranti District, Riau, Indonesia - Ayulia, Liska; Djoefrie, MHB; Arifien, Yunus (Journal of Tropical Crop Science, 2021)
Sago (Metroxylon spp.) is the world’s highest starch producer that have high productivity. Sago starch, however, is still underutilized compared to other starch. Sago can produce dry starch of 20-40 ton per ha per year. Indonesia has the largest sago area in the world with more than 90% of the world’s total sago area. Sago have high species diversity and not all of them have the same starch-producing capability. This research was conducted to gather information on the morphological characters and starch production potentials of several types of sago in Meranti Islands Regency, Riau Province, Indonesia, especially in Bandul, Mengkirau, Tanjung Peranap, and Bagan Melibur. Three different types of sago in Kepulauan Meranti Regency, Riau, has been identified, namely Beremban, Meranti and Sangka. The morphology and starch production of different types of sago vary depending on environmental conditions, including soil types. Beremban Sago collected from Bandul Village were found to have the highest starch content, therefore it has potentials to be developed for starch production in Indonesia.